Interactive Effects of [CO2] and Temperature on Plant Chemistry of Transgenic Bt Rice and Population Dynamics of a Non-Target Planthopper, Nilaparvata lugens (Stål) under Different Levels of Soil Nitrogen - Yanmin Liu; Zhihao Dang; Yanhui Wang; Megha N. Parajulee; Fajun Chen (Toxins, 2019)
Gaining a better understanding of the interactive effect of projected atmospheric CO2 level increase and the Earth’s rising temperature on plant chemistry (nutritional and defensive characteristics) of transgenic crops is essential when attempting to forecast the responses of target and non-target insects to climate change. In this study, effects of carbon dioxide (CO2; elevated versus ambient), temperature (T; high versus low), and their interactions on leaf nitrogen content (N%) and C:N ratio of transgenic Bt rice and its non-Bt isoline grown under low- and high-N fertilizer were systematically analyzed together with the resulting insect population dynamics of a non-target planthopper Nilaparvata lugens (Stâl) in open-top-chamber experiments. The results indicated that under low-N treatment, elevated CO2 at low T (i.e., eCO2) (compared to ambient CO2 at low T, i.e., CK) significantly decreased N% and Bt-toxin content and significantly increased C:N ratio in leaf sheath and leaf of Bt rice, especially during the tillering stage, whereas inverse effects of high T were shown on the plant chemistry of Bt rice, especially during heading stage. The combination of elevated CO2 and high T (i.e., Combined) (in contrast to CK) significantly increased N% and decreased C:N ratio in leaf sheath of Bt rice during the heading stage under low-N fertilizer, while significantly decreased N% and increased C:N ratio in leaf of Bt rice during the tillering stage, regardless of fertilizer-N level, and significantly increased Bt-toxin content in leaf sheath and leaf during the tillering stage under both low- and high-N. Moreover, no discernable relationships between Bt-toxin content and N% or leaf C:N ratio were observed at any CO2 or N levels evaluated. Furthermore, transgenic treatment, temperature and fertilizer-N level interactions, and CO2 and fertilizer-N level interactions all significantly affected the population dynamics of N. lugens. Specifically, high-N significantly enhanced the population dynamics of N. lugens fed on non-Bt rice grown under eTemp and Bt cultivar significantly reduced the population dynamics of N. lugens under eCO2 regardless of N fertilizer levels. The study demonstrates that the planting of transgenic Bt rice would not increase the risk of increased N. lugens severity under the combined condition of elevated CO2 and increased temperature, particularly under moderate level of N fertility.